Resistência ao desgaste abrasivo da liga Fe66B30Nb4 processada por conformação por spray - Catto, Fausto Lopes (2009)
Aiming at the improvement of the wear resistance of a glass former composition, the Fe66B30Nb4, the alloy was modified with the addition of Ti, resulting in the theoretical compositions: Fe63B29Nb4Ti4 (SF1) and Fe65B30Nb4Ti1 (SF2). These compositions were spray formed from the melts into two small deposits each one with different set of processing parameters. The crystalline microstructures obtained were characterized by optical microscopy, SEM/EDS, XRD, DSC and chemical analysis of Nb, Ti (by optical spectroscopy) and N (by thermal conductivity). Also, a melt spun ribbon was produced with the Fe65B30Nb4Ti1 alloy. This procedure provided some information about metastable phases which could form in the deposits: borides, sub-borides and amorphous phase. Finally, several hardness and DSRW wear tests were conducted. Materials weight losses were discussed in comparison to high chromium white cast iron. The spray formed deposit of Fe65B30Nb4Ti1, produced with the SF2 parameters set up, presented 51% less mass loss when comparing with high chromium white cast iron. The rapidly cooled Fe63B29Nb4Ti4 alloy presented a worse wear resistance result than the slowly cooled Fe65B30Nb4Ti1 alloy. Some factors which could have influenced these results were discussed.